The Effect of Chitosan Coating on the Spores Germination of Penicillium fimorum and its Ability to Inhibit Ochratoxin A Production - Manar Mahmood Al-Ahmed / Mohammed Amer Fayyadh / and Labeed Abdullah Al-Saad ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
This study was conducted in the Department of Plant Protection/College of Agriculture/University of Basrah. This study aimed to evaluating the ability of chitosan coating using different concentrations to inhibit the spores germination of P. fimorum as well as its ability to inhibit Ochratoxin A production. The results showed that using both of micro and nano-chitosan coating causes decreasing on the spores germination of P. fimorum, however the effect of chitosan varied with the difference of the used concentrations, as the concentration of 2000ppm completely inhibited the spores germination of P. fimorum, compared with control and acetic acid treatments, which achieved about 41.66 × 106 and 24.33 × 106 of the number of colony-forming units (Cfu), respectively. The results of the statistical analysis of the interaction between the chitosan types and the concentrations showed a significant effect on the spores germination rates, as micro-chitosan completely inhibited the spores germination of P. fimorum by using 100ppm concentration, compared with 3 × 106 in the nano-chitosan treatment. Moreover, the results showed that using both types of chitosan coating achieved 100% of inhibition rates for Ochratoxin A productions.